Obstacles to Scientific Research from the Point of View of Graduate Students at the Faculty of Physical Education and Sport Sciences, University of Tripoli - Alayuri, Abdurazag Khalifa; Jalid, Mohamed Chadli (Advances in Social Sciences Research Journal, 2024)
This research aimed to identify the obstacles to scientific research from the point of view of graduate students at the Faculty of Physical Education and Sport Sciences at Tripoli University related to faculty members, related to graduate students, and related to the administrative side and supervision, the researcher used the descriptive method by survey method due to its suitability to the nature of this research, the research sample was selected randomly, where the total number of the sample amounted to (77) students with a percentage of (48%), and the most important findings of this research were that the responses of the sample members towards the dimensions of The most important findings of this research were that the responses of the sample members towards the dimensions of the axis of obstacles to scientific research from their point of view were realistic and were not due to chance, and the results of the responses of the research sample towards the stability coefficients of the axis of obstacles to scientific research ranged from (73% to 83%), and that the overall stability scores for the axis as a whole amounted to (84%), which are high stability scores.